Confluent territories and overlapping sovereignties: Britain's nineteenth-century Indian empire in the Kumaon Himalaya - Bergmann, Christoph (Journal of historical geography, 2016)
This article provides a locally grounded understanding of how geographies of sovereignty became established and called into question on the external frontiers of British imperial expansion. The empirical case study focuses on the Bhotiyas, trans-Himalayan traders who reside in several high valleys of the Kumaon Himalaya in today's North Indian state of Uttarakhand. When the British East India Company annexed that region in 1815 it was recognized as a so-called Non-Regulation Province. Through a close examination of British interactions with Kumaon's traders, the paper will reveal the frictions that arose from this exceptional legal status. This focus serves to address the broader question of how sovereign claims work through multiple and shifting articulations. The paper first considers the establishment of Kumaon as a Non-Regulation Province by attending to the strategies of British administrators in gaining the loyalty of its trans-Himalayan traders, particularly after the Dogras' invasion of western Tibet in 1841. Subsequently, attention turns toward the negotiations between colonial administrators, Tibetan authorities and the Bhotiyas over taxation, which highlights British efforts to fit this mountainous periphery into the empire's standard grid during the 1890s. The analysis considers a previous call to conceive High Asia as a continuous zone and an agentive site of political action by arguing that confluent territories and overlapping sovereignties are key to understanding imperial frontiers. As such the article contributes to scholarship that deals with the anomalous spaces of Britain's Indian empire, including both the jurisdictional and everyday politics in the margins.